Elvis Presley press conference (Module II, 2013)
USA. More footage of the Elvis Presley press conference: Presley talks about the popularity of Rock and Roll. When asked if he would take the wiggle out of his music, as it is considered to be immoral, Elvis responds, "take the wiggle out of it, it's finished". Presley is also questioned on his time in the Army, being a celebrity in the service, his hair and his unpopularity. Clip ends with Presley waving as he boards ship.